The Play Supplementary Reading Material - Hunt, Roderick (China Oxford University Press, 2012)
In The Play, Mrs May reads The Wizard of Oz to her class on a rainy day. The story captivates the children, who begin acting it out during free time. Recognizing their enthusiasm, Mrs May helps them turn it into a real class play. The children prepare costumes and sets, and parents are invited to watch the performance. The story emphasizes teamwork, creativity, and the joy of storytelling through drama. It concludes with appreciation for the children's efforts and Mrs May$1 (Bs guidance.s
This short, funny tale$1 (Btypical of Level 4 stories$1 (Bis designed to support early readers by blending repetition and recognizable characters to reinforce vocabulary and comprehension. Children especially enjoy reading it multiple timess